EVALUATION OF PARTIAL FISH MEAL SUBSTITUTION BY FERMENTED SOYBEAN MEAL ON GROWTH, ANTIOXIDANT AND IMMUNE STATUS OF Labeo rohita - Nudrat Aslam; Dr Abdul Mateen; Shakeela parveen (Journal of Animal and Plant Sciences, 2025)
Due to the increase demand, market instability and the high price of fish meal (FM), the aqua-feed industry must find alternative protein sources to reduce its reliance on FM and to ensure cost-effective aqua-feed production. Due to its high protein content, soybean meal (SBM) can substitute costly FM in fish feed. This research evaluated the effects of substituting FM with SBM and fermented soybean meal (FSBM), supplemented with lysine and methionine, on growth performance, body composition, antioxidant enzyme activity and immune competency of Labeo rohita. Fingerlings (10.9 ±0.4g) were acclimatized for two weeks and divided into seven groups, each with three replicates. Seven experimental diets were formulated, replacing 0 (control diet), 25%, 50% %, and 75% FM with SBM and FSBM (SBM-25, SBM-50, SBM-75, FSBM-25, FSBM-50 and FSBM-75). In the present study, Lactobacillus plantarum was used to ferment SBM. Fish were fed two times a day for 4 months under laboratory conditions. Results showed that fermentation significantly improved the nutritional quality of SBM by reducing anti-nutritional factors (trypsin, glycinin, and β-conglycinin). The replacement of 25% FM with SBM and FSBM did not significantly affect growth performance compared to the control. However, a substantial decrease in weight gain (WG) and specific growth rate (SGR) was observed as FM replacement increased to 50% and 75%, with the lowest WG and SGR recorded in SBM-75 and FSBM-75 groups. Activities of antioxidant enzymes (SOD and CAT) and immune parameters (WBCs and IgM) decreased significantly in 75% SBM and FSBM groups compared to the control. The FSBM diets did not affect whole-body crude protein, fat and moisture content. However, SBM-75 diets significantly enhanced whole-body moisture content while reducing crude protein content. These results indicate that SBM and FSBM can replace 25 and 50% of FM with additional lysine and methionine supplementation without compromising growth and physiological health.
Keywords: Fermented soybean meal (FSBM); Anti-nutritional factors (ANF); Labeo rohita; immune competency; enzymatic indices